Near-field head-related transfer-function measurement and database of human subjects - Yu, Guangzheng; Wu, Ruixing; Liu, Yu; Xie, Bosun (The Journal of the Acoustical Society of America, 2018)
Near-field head-related transfer functions (HRTFs) of human subjects are essential to those researching spatial hearing. By using a carefully designed measurement system, near-field HRTFs of human subjects were measured and a database was constructed. The database includes 56 Chinese human subjects, seven source distances from 0.2 to 1.0 m, and 685 directions at each distance for each subject. In the present work, the technique of near-field HRTF measurement is outlined, the performance of the measurement system is assessed and validated, and the resultant database is reported. The database can provide fundamental data for future research.